Champions of winter survival: cold acclimation and molecular regulation of cold hardiness in evergreen conifers. Issue 2 (27th September 2020) - Chang, Christine Yao‐Yun; Bräutigam, Katharina; Hüner, Norman P. A.; Ensminger, Ingo
Summary: Evergreen conifers are champions of winter survival, based on their remarkable ability to acclimate to cold and develop cold hardiness. Counterintuitively, autumn cold acclimation is triggered not only by exposure to low temperature, but also by a combination of decreasing temperature, decreasing photoperiod and changes in light quality. These environmental cues control a network of signaling pathways that coordinate cold acclimation and cold hardiness in overwintering conifers, leading to cessation of growth, bud dormancy, freezing tolerance and changes in energy metabolism. Advances in genomic, transcriptomic and metabolomic tools for conifers have improved our understanding of how trees sense and respond to changes in temperature and light during cold acclimation and the development of cold hardiness, but there remain considerable gaps deserving further research in conifers. In the first section of this review, we focus on the physiological mechanisms used by evergreen conifers to adjust metabolism seasonally and to protect overwintering tissues against winter stresses. In the second section, we review how perception of low temperature and photoperiod regulate the induction of cold acclimation. Finally, we explore the evolutionary context of cold acclimation in conifers and evaluate challenges imposed on them by changing climate and discuss emerging areas of research in the field.